SYSTEMATIC LITERATURE REVIEW: EXPLORATION OF FACTORS THAT INFLUENCE INNOVATION PERFORMANCE AND MANUFACTURING COMPANY PERFORMANCE - Lithrone Laricha Salomon; Agustinus Purna Irawan; Eko Suhartanto (Graduate Program of Universitas Tarumanagara, 2024)
This research literature review that reviews the literature on the factors that influence innovation variables has been a lot, but those that review innovation performance variables are relatively still not much. Therefore, the literature review in this study aims to investigate the factors that affect innovation performance in manufacturing companies, as well as factors that act as mediation and moderation. The Systematic Literature Review (SLR) method is used in this study to analyze and review or look back at findings that are systematically identified based on previous research evidence related to factors that affect the innovation performance of manufacturing companies. Research data was obtained from Google Scholar with a time span of 2015-2023. Findings on journal searches found 304 articles. Based on the search for articles that discuss and focus on factors that affect the specific innovation performance of manufacturing companies, 25 articles were found. The article is used as a data source and will be examined in more depth. The results of the research found that (1) Various factors affect innovation performance in manufacturing companies; (2) Several factors can mediate and moderate exogenous (independent) variables on the innovation performance of manufacturing companies; and (3) Various theories have been used in research on the innovation performance of manufacturing companies. Therefore, manufacturing companies can use the above variables as factors that can be used to improve innovation performance to increase productivity, effectiveness, and can drive growth for manufacturing companies. These findings can be used as reference material for further research on variables that are able to mediate and moderate the relationship between exogenous variables on innovation performance in manufacturing companies and the theory used.